Structural integrity analysis of transmission structure in flapping-wing micro aerial vehicle via 3D printing. (February 2019) - Chen, Zuyong; Xu, Jun; Liu, Binghe; Zhang, YanLai; Wu, Jianghao
Abstract: 3D printing makes the small and compact transmission system of flapping-wing micro aerial vehicle (FMAV) available for in-house designs and tests. However, the high flapping frequency requiring stringent strength integrity and fatigue longevity for the structure itself always serves as the major responsible reason for the structural failure of FMAV. In this paper, experiment as well as numerical computation efforts were acted in concert to gain an insightful understanding of the failure mechanism for the transmission structure of FMAV. Firstly, a FMAV structure was fabricated by 3D printing using Ultraviolet(UV) Cureable Resin. The isotropic constitutive behavior of the resin was evaluated and confirmed. Further, numerical computation model describing the mechanical behavior of FMAV structure was established and verified by experiments. Secondly, together with the computational structural model and constitutive model, the dynamic response of the transmission structure subject to high frequency flipping motion was described. Both simulation and experiments share the same failure mode and configuration and the dominate factor for the failure was found out to be the excessive bending deformation. Finally, design parametric study along with different boundary conditions aiming at the future ground testing were conducted to uncover the governing influences over the transmission structure integrity. Results may shed lights on the structural integrity design of FMAV and pave a new road for future advanced FMAV design, manufacturing and testing. Highlights: A finite element modeling methodology for transmission system of FMAV was presented. The dominate factor for the failure of the transmission structure was uncovered. Impacts of different boundary conditions on the structural strength were discussed. Improvement design of the main components were carried out.